New graduate physiotherapists' perceptions and experiences working with people from culturally and linguistically diverse communities in Australia: a qualitative study. (3rd June 2022) - Te, Maxine; Blackstock, Felicity; Liamputtong, Pranee; Chipchase, Lucy
ABSTRACT: Introduction: Upon entering the workforce, physiotherapists are required to provide safe and effective care toward people from culturally and linguistically diverse (CALD) communities. Objective : To explore new graduate physiotherapists' perceptions and experiences when working with people from CALD communities in Australia. Methods: A phenomenological framework guided this qualitative study. Seventeen new graduate physiotherapists who had experience working with people from CALD communities were interviewed. Interviews were audio-recorded, transcribed verbatim, and then thematically analyzed. Results: New graduate physiotherapists felt challenged when they encountered people from CALD communities. Although they had good intentions, their healthcare approach was limited. Their perceived approach to care was unidirectional and anchored in a western healthcare framework, and they used superficial strategies for cultural adaptation. Perceptions that people from CALD communities were passive recipients to healthcare also underpinned their practices. While participants described pockets of patient-centered care, their perceived healthcare approach lacked appropriate consideration and integration of their patients' cultural perspective. Conclusion: New graduate physiotherapists may need support with effectively integrating different cultural perspectives into their care and adapting their practices and interventions for people from CALD communities. Education and training at entry-level and after graduation should address these learning needs. However, there is limited research on how to culturally adapt physiotherapy practices and interventions that impact patient engagement outcomes. Thus, research is needed to understand how current evidence-based interventions can be culturally adapted to integrate patients' cultural perspectives into care.